Wheat yield potential can be maximized by increasing red to far‐red light conditions at critical developmental stages. (19th July 2022) - Dreccer, Maria Fernanda; Zwart, Alec B.; Schmidt, Ralf‐Christian; Condon, Anthony G.; Awasi, Mary A.; Grant, Terry J.; Galle, Alexander; Bourot, Stephane; Frohberg, Claus
Abstract: Sensing of neighbours via the Red to Far‐Red light ratio (R:FR) may exert a cap to yield potential in wheat. The effects of an increased R:FR inside the canopy were studied in dense wheat mini canopies grown in controlled environments by lowering FR. To distinguish between effects exerted by light sensing and assimilate supply, the treatments were complemented with elevated CO2, applied between different developmental timepoints to specifically impact tillering, spike growth, floret fertility and grain filling, in different combinations. The yield response to high R:FR was strongly dependent on the developmental stage in all three cultivars and pivoted between positive if applied after the start of stem elongation, and negative or null if applied before. Yield gains of up to 70% and 120% were observed, respectively, in two cultivars, associated with a higher number of tiller spikes and grains per spike in the main shoot. The response to the combination of high R:FR and elevated CO2 or CO2 alone were cultivar dependent. Taken together, our results suggest that R:FR exerts a significant control on yield potential in wheat and achieving a high R:FR from stem elongation to maturity is a promising lever towards a significant increase in grain yield. Abstract : "We demonstrate light quality is crucially important for wheat yield potential. Our study, using dense mini‐canopies under controlled conditions, shows a High Red:Far Red ratio (due to lower Far Red) during spike growth and grain filling almost doubles grain yield, probably by disrupting the perception of neighbours."